2005
DOI: 10.1007/s11273-004-0413-2
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Holocene Mangrove Development and Relative Sea-level Changes on the Bragança Peninsula (Northern Brazil)

Abstract: Based on the integration of geological information, the pollen record, radiocarbon data, and modern mangrove distribution, this paper proposes a model of evolutionary development for mangroves on the Brazilian Braganc¸a Peninsula driven by relative sea-level changes from the middle to late Holocene. After a postglacial relative sea-level rise (RSL), the mangrove habitats on the Braganc¸a Peninsula began to develop at about 5100 years BP close to the current RSL, originating in the middle of the peninsula. Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 30 publications
6
82
0
15
Order By: Relevance
“…Although distribution models usually perform well in characterizing and predicting current distributions (Franklin and Miller 2009), a number of issues have been raised in regards to the lack of important ecological processes and the methodological issues of such models (e.g., Dawson 2003, Record et al 2013). Previous mangrove species distribution modeling research has been performed at geographic extents much smaller than the ranges of the species modeled (Cohen et al 2005, Gilman et al 2007). The work presented here is the first application of species and community distribution modeling to provide a first approximation of how future climate-change scenarios will influence global distributions of mangrove species and assemblages at geographic extents encompassing the entirety of species' ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although distribution models usually perform well in characterizing and predicting current distributions (Franklin and Miller 2009), a number of issues have been raised in regards to the lack of important ecological processes and the methodological issues of such models (e.g., Dawson 2003, Record et al 2013). Previous mangrove species distribution modeling research has been performed at geographic extents much smaller than the ranges of the species modeled (Cohen et al 2005, Gilman et al 2007). The work presented here is the first application of species and community distribution modeling to provide a first approximation of how future climate-change scenarios will influence global distributions of mangrove species and assemblages at geographic extents encompassing the entirety of species' ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mangrove modeling research has focused on topics such as mangrove demography (Clarke 1995), distributions (Cohen et al 2005), stand dynamics (Chen and Twilley 1998, Twilley et al 1999, Berger and Hildenbrandt 2000 individual-based models reviewed by Berger et al 2008), ecosystem function and services (Heald 1971, Grasso 1998, and food webs (Odum and Heald 1975) at geographic extents much smaller than the range of a species. Here we use SDMs and CDMs to explore how mangrove biodiversity may respond to global climatic change at large spatial extents encompassing the entirety of species' ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Colinvaux and De Oliveira 2000, Vital and Stattegger 2000, Maslin et al 2000. Thus, interchanges between dry and wet periods may have significant impacts on coastal wetland, as they modify the soil salinity gradients and the soil moisture (Cohen et al 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Koenig et al 2007). Recent events, such as the Holocene fluctuations in sea level with the associated changes in the sedimentation patterns of the Amazon basin, modified the distribution of mangrove ecosystems on the northern coast of Brazil (Cohen et al 2005). Furthermore, human impacts on these environments over the past few centuries may have contributed to the loss of habitats in this region (Behling et al 2001), which is reflected in the low genetic diversity observed in the present study.…”
Section: Genetic Variationmentioning
confidence: 63%